Synthesis, biological evaluation, and molecular modelling studies of potent human neutrophil elastase (HNE) inhibitors - Maria Paola Giovannoni (Journal of Enzyme Inhibition and Medicinal Chemistry, 2018)
We report the synthesis and biological evaluation of a new series of 3- or 4-(substituted)phenylisoxazolones as HNE inhibitors. Due to tautomerism of the isoxazolone nucleus, two isomers were obtained as final compounds (2-NCO and 5-OCO) and the 2-NCO derivatives were the most potent with IC50 values in the nanomolar range (20–70 nM). Kinetic experiments indicated that 2-NCO 7d and 5-OCO 8d are both competitive HNE inhibitors. Molecular modelling on 7d and 8d suggests for the latter a more crowded region about the site of the nucleophilic attack, which could explain its lowered activity. In addition molecular dynamics (MD) simulations showed that the isomer 8d appears more prone to form H-bond interactions which, however, keep the reactive sites quite distant for the attack by Ser195. By contrast the amide 7d appears more mobile within the active pocket, since it makes single H-bond interactions affording a favourable orientation for the nucleophilic attack.